Fabulous modern cookies : lessons in better baking for next-generation treats - Taylor, Christopher A., 1982-; Arguin, Paul M. (The Countryman Press, A division of W. W. Norton & Company Independent Publishers since 1923, 2022)
"With bolder-than-ever flavors and spectacularly scientific techniques, cookies have truly never been more fabulous. Chris Taylor and Paul Arguin bring fresh perspective and heaps of creativity to everything they bake. Now reinventing America's most traditional handheld dessert-the cookie-they offer 100 reliable and exciting recipes that are sure to impress. From Salted Honey Drops to Black-Bottom Lemon Squares, and Coffee Bean Crunchers to Bronze Butter Chocolate Chip Cookies, these are next-level cookies. Combining their passion for serious baking with their professional backgrounds as accomplished scientists, Arguin and Taylor apply new methods and rationales for ingredient pairings adapted from food science texts to develop novel base recipes and innovative techniques. In these pages, they share what they've learned in lively tips and tricks for every recipe and style of cookie. Complete with mouthwatering photos, options to make ahead, decorate, or indefinitely adapt, these outside-the-box recipes are the very definition of fabulous"--